Significantly enhanced dielectric and energy storage properties of plate-like BN@BaTiO3 composite nanofibers filled polyimide films. (December 2019) - Wan, Baoquan; Yue, Shuangshuang; Li, Haiyu; Liu, Yunying; Zhang, Qiwei
Graphical abstract: Highlights: The novel plate-like BN and BT composite structured fiber was successfully fabricated by an improved electrospinning. The introduction of composite fibers can effectively improve the dielectric and energy storage properties of films. The composite films show a maximum energy density (Ue = 7.1 J/cm 3 ), which is about three times greater than that of PI. Abstract: In this study, a new type of plate-like boron nitride (BN) and barium titanate (BT) composite nanofiber (BN@BT) was fabricated by an electrospinning technology, and introduced into polyimide (PI) matrix to form nano-composite films by in-situ polymerization method. The composite film with 20 wt% BN@BT-fiber shows a high dielectric constant of ε r  = 47.57 and a low dielectric loss of tg δ  = 0.0334 at room temperature. When the content of BN@BT-fiber is up to 1 wt%, the composite film exhibits a maximum energy storage density of Ue  = 7.1 J/cm 3 at 3438 kV/cm, which is about three times greater than that of PI (≈2.4 J/cm 3 at 3628 kV/cm). Meanwhile, the plate-like boron nitride (BN) also enables the composite film to have an improved heat dissipation and thermal stability, and then improves the breakdown field strength.